Unerwünschte und erwünschte Pigmentierung = Undesirable pigmentation - Bayerl, Christiane (Der Hautarzt, 2015)
BackgroundHomogenous pigmentation can be induced by α-melanocyte-stimulating hormone (MSH) homologues. Cosmetically inacceptable pigmentation is mostly located on the face.ObjectivesAlthough afamelatonide is a prescription drug for the orphan disease erthropoetic protoporphyria, structurally related α-MSH derivatives are available via the internet. Preventive and therapeutical options are necessary for postinflammatory hyperpigmentation, melasma, and lentigines.MethodsCase reports address activation of dysplastic naevi by melanotan I. Wood's lamp is of some use in analyzing the level of hyperpigmentation. However, no guidelines have been established; thus, a summary of current studies is presented.ResultsMelanotan I leads to the activation of dysplastic nevi. The gold standard for hyperpigmentation is triple therapy with hydrochinon, tretinoin, and steroids, which can cause irritation and lead to ochronosis in some individuals. Tyrosinase inhibitors, substances that increase the cell turnover, and plant derivatives are less efficient but more tolerable.ConclusionsMelanotan I and bleaching creams, which may possibly contain mercury, are dangerous. Hyperpigmentation is best treated using a combination therapy that inhibits melanocyte activity and melanin synthesis, removes melanin, destroys melanin granules, and includes UV protection. Especially in Fitzpatrick skin types IV-VI, cryotherapy and laser are not the first line treatment options due to renewed posttreatment hyperpigmentation.
Gesehen am 11.12.2018